A 3-Dimensional Classification for Degenerative Glenohumeral Arthritis Based on Humeroscapular Alignment. Issue 8 (11th August 2022) - Kleim, Benjamin D.; Hinz, Maximillian; Geyer, Stephanie; Scheiderer, Bastian; Imhoff, Andreas B.; Siebenlist, Sebastian
Background: Seminal classifications of degenerative arthritis of the shoulder (DAS) describe either cuff tear arthropathy in the coronal plane or primary osteoarthritis in the cross-sectional plane. None consider a biplanar eccentricity. Purpose/Hypothesis: The purpose of this study was to investigate humeroscapular alignment (HSA) of patients with DAS in both the anteroposterior (A-P) and superoinferior (S-I) planes on computed tomography (CT) after 3-dimensional (3D) reconstruction and develop a classification based on biplanar HSA in 9 quadrants. It was hypothesized that biplanar eccentricity would occur frequently. Study Design: Cross-sectional study; Level of evidence, 3. Methods: The authors analyzed 130 CT scans of patients who had undergone shoulder arthroplasty. The glenoid center, trigonum, and inferior angle of the scapula were aligned in a single plane using 3D reconstruction software. Subluxation of the HSA was measured as the distance from the center of rotation of the humeral head to the scapular axis (line from trigonum through glenoid center) and was expressed as a percentage of the radius of the humeral head in both the A-P and the S-I directions. HSA was described in terms of A-P alignment first (posterior/central/anterior), then S-I alignment (superior/central/inferior), for a total of 9 different alignment combinations. Additionally, glenoid erosion was graded 1-3. Results: Subluxation of the HSA was 74.1% posterior to 23.5% anterior in the A-P direction and 17.2% inferior to 68.6% superior in the S-I direction. A central HSA was calculated as between 20% posterior to 5% anterior (A-P) and 5% inferior to 20% superior (S-I), after a graphical analysis. Posterior subluxation >60% of the radius was labeled as extraposterior, and static acetabularization was labeled as extrasuperior. Overall, 21 patients had central-central, 40 centrosuperior, and 1 centroinferior alignment. Of 60 shoulders with posterior subluxation, alignment was posterocentral in 31, posterosuperior in 25, and posteroinferior in 5. There were 3 patients with anterocentral and 4 anterosuperior subluxation; in addition, 4 cases with extraposterior and 17 with extrasuperior subluxation were identified. Conclusion: There was a high prevalence of biplanar eccentricity in DAS. The 3D classification system using combined HSA and glenoid erosion can be applied to describe DAS comprehensively.